Research of the photo-voltaic effect in the two-base Ag-N⁰AlGaAs-n⁺GaAs-n⁰GaInAs-Au structure with various thicknesses of a base - Yodgorova, D.M.; Karimov, A.V.; Giyasova, F.A.; Karimova, D.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The results of research of photoelectric phenomena in the two-base Ag-N⁰AlGaAs-n⁺GaAs-n⁰GaInAs-Au structure are presented. The photo-voltaic effect
observable in a wide range of the spectrum (0.4-2 µm) is explained by different signs of
the photo EMF created by the separation of photocarriers in the energy barrier and from
the levels of intrinsic defects as well as deep impurities of oxygen in the quasineutral
base. A mechanism of photosensitivity of thin base structures with Schottky-Mott’s
barrier under photovoltaic conditions is offered.